2012
DOI: 10.4236/ns.2012.412129
|View full text |Cite
|
Sign up to set email alerts
|

Influence of volatile degassing on initial flow structure and entrainment during undersea volcanic fire fountaining eruptions

Abstract: Release of dissolved volatiles during submarine fire fountaining eruptions can profoundly influence the buoyancy flux at the vent. Theoretical considerations indicate that in some cases buoyant magma can be erupted prior to fragmentation (~75% vesicle volume threshold). Laboratory simulations using immiscible fluids of contrasting density indicate that the structure of the source flow at the vent depends critically on the relative magnitudes of buoyancy and momentum fluxes as reflected in the Richardson number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Models of submarine eruptions emphasize the influence of volatile degassing on initial flow structure and entrainment during undersea volcanic eruptions (Friedman et al 2012). Release of dissolved volatiles during submarine fire fountaining eruptions can profoundly influence the buoyancy flux at the vent, and experimental simulations by Friedman et al (2012) demonstrate that a submarine eruption discharge can take dramatically different forms, such as fire fountaining or passive effusive discharges, depending on the relative contributions of momentum and buoyancy at the source vent. Thus, the bulk density and, consequently, the positive buoyancy flux with respect to surrounding seawater of the erupting mixtures are (Friedman et al 2007).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Models of submarine eruptions emphasize the influence of volatile degassing on initial flow structure and entrainment during undersea volcanic eruptions (Friedman et al 2012). Release of dissolved volatiles during submarine fire fountaining eruptions can profoundly influence the buoyancy flux at the vent, and experimental simulations by Friedman et al (2012) demonstrate that a submarine eruption discharge can take dramatically different forms, such as fire fountaining or passive effusive discharges, depending on the relative contributions of momentum and buoyancy at the source vent. Thus, the bulk density and, consequently, the positive buoyancy flux with respect to surrounding seawater of the erupting mixtures are (Friedman et al 2007).…”
Section: Discussionmentioning
confidence: 98%
“…As with sub-aerial eruption clouds, mathematical models shown that entrainment conditions play an important role in the shape and geometry of ascending volcanic material (Suzuki et al 2005). Models of submarine eruptions emphasize the influence of volatile degassing on initial flow structure and entrainment during undersea volcanic eruptions (Friedman et al 2012). Release of dissolved volatiles during submarine fire fountaining eruptions can profoundly influence the buoyancy flux at the vent, and experimental simulations by Friedman et al (2012) demonstrate that a submarine eruption discharge can take dramatically different forms, such as fire fountaining or passive effusive discharges, depending on the relative contributions of momentum and buoyancy at the source vent.…”
Section: Discussionmentioning
confidence: 98%
“…Fluidal shapes observed in ash‐sized pyroclasts (supporting information Figures S4 and S6) have been observed in submarine basaltic eruptions ranging from Strombolian to Hawaiian in eruptive styles [ Clague et al ., , ; Conte et al ., ]. These magmas are at the appropriate depth range (<200 m) at which explosions driven by magmatic volatiles may be expected to occur for such compositions [ Head and Wilson , ; Friedman et al ., ]. Explosive activity of this kind was periodically observed in both the first phase and until late January during the second phase, as evidenced by large upwelling and at the sea surface and the formation of huge bursting bubbles >15 m high [ Carracedo et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon, where the bulk density of magma plus gas bubbles is less than the surrounding environment (water) prior to fragmentation, can never be obtained in the subaerial environment and is likely to lead to novel eruptive behavior in the submarine realm [e.g. Friedman et al, 2012;Rotella et al, 2013].…”
Section: Eruption Mechanism On the Seafloormentioning
confidence: 99%